(untitled) - Kottak, Canrad Phillip (New York, NY, 2012)
This book introduction to cultural anthropology carefully balances coverage of core topics with contemporary changes in the field. Since no single or monolithic theoretical perspective orients this book, instructors with a wide range of views and approaches can use it effectively. The combination of brevity and readability make Mirror for Humanity a perfect match for cultural anthropology courses that use readings or ethnographies along with a main text
Keywords: Ethnology,Nhân chủng học